Arabidopsis transcription factor WRKY8 functions antagonistically with its interacting partner VQ9 to modulate salinity stress tolerance. (1st April 2013) - Hu, Yanru; Chen, Ligang; Wang, Houping; Zhang, Liping; Wang, Fang; Yu, Diqiu
Summary The WRKY transcription factors have been demonstrated to play crucial roles in regulating stress responses; however, the exact mechanisms underlying their involvement in stress responses are not fully understood. Arabidopsis WRKY8 was predominantly expressed in roots and was highly upregulated by salt treatment. Disruption of WRKY8 rendered plants hypersensitive to salt, showing delayed germination, inhibited post‐germination development and accelerated chlorosis. Further investigation revealed that WRKY8 interacted with VQ9, and their interaction decreased the DNA‐binding activity of WRKY8. The VQ9 protein was exclusively localized in the nucleus, and VQ9 expression was strongly responsive to NaCl treatment. Mutation of VQ9 enhanced tolerance to salt stress, indicating that VQ9 acts antagonistically with WRKY8 to mediate responses to salt stress. The antagonist functions of WRKY8 and VQ9 were consistent with an increased or reduced Na+/K+ concentration ratio, as well as contrasting expression patterns of downstream stress‐responsive genes in salt‐stressed wrky8 and vq9 mutants. Moreover, chromatin immunoprecipitation (ChIP) assays showed that WRKY8 directly bound the promoter of RD29A under salt conditions. These results provided strong evidence that the VQ9 protein acts as a repressor of the WRKY8 factor to maintain an appropriate balance of WRKY8‐mediated signaling pathways to establish salinity stress tolerance.